Pengaruh Terapi Relaksasi Nafas Dalam Terhadap Tingkat Kecemasan Dan Lama Persalinan Kala I Dan II Di BPM Wilayah Klaten - Henik Istikhomah; Murwati Murwati (Interest : Jurnal Ilmu Kesehatan, 2016)
Abstract: Deep Relaxation Therapy, Level Anxiety And Prolong Duration Labor Stage. Patients who will give birth had experienced psychological problems that cause form the emotional reaction as the manifestation of psychological symptoms, the actions to be carried out either surgery or childbirth aid measures constitute a potential or actual threat to the integrity of someone who can evoke physiological and psychological stress. This emotional reaction usually is generally a negative reaction, such as refuse, fear, anger, sadness, and anxiety. Giving deep breathing relaxation techniques in patients will be a decrease in tension, feeling amazingly beautiful in controlling body functions so that labor becomes smooth. Purpose of this study was to determine the effect of therapy on the breath in anxiety level and duration of labor. The design of this study using the pre and post-test only one group. analysis techniques with Wilcoxon test. using purposive sampling technique with 25 respondents. Univariate analysis results mean pre-test anxiety at 43.16 and the average post-test by 31. The mean duration of the first labor stage of the intervention group is 504 minutes and 564 minutes at control group. The Mean duration of second labor stage of the intervention group is 140 minutes and the control group was 57 minutes. Bivariate test results there is the influence between deep breathing relaxation therapy interventions with anxiety with a p value= 0.001, there is the influence of deep breathing relaxation techniques with the duration of first labor stage with p-value = 0.001, no effect of deep breathing relaxation with the duration of second labor stage with p = 0:59. In conclusion, there is the influence of deep breathing relaxation therapy to anxiety and the duration of the first stage of labor time, there is no influence therapy relaxation with the duration of the second labor stage.